Adventure activities and environmental education in Physical Education journals - De Paula Figueiredo, Juliana [UNESP]; Schwartz, Gisele Maria [UNESP] (FapUNIFESP (SciELO), 2013)
This qualitative study aimed at analyzing the articles that deal with different approaches and methodological strategies linking the themes of adventure activities and environmental education in journals of Physical Education area. An exploratory research was conducted in journals with A concept in 2011 WebQualis CAPES platform. The results show that this relationship is few explored in the area and the studies emphasize only some aspects, requiring therefore new approaches.
Atividades de aventura e educação ambiental como foco nos periódicos da área de Educação Física 1
Keywords: Adventure Activities; Environmental Education; Physical Education